Preparation for anesthesia of patients with concomitant lung pathology and a high risk of developing postoperative pulmonary complications - K. N. Khrapov; M. G. Kovalev; S. S. Sedov (Вестник анестезиологии и реаниматологии, 2020)
The objective: basing on published data, to highlight the main issues of preparation of patients with concomitant lung pathology and a high risk of developing postoperative pulmonary complications for planned surgical interventions.Results: changes made to international guidelines over the past 5 years based on evidence-based studies and meta-analyzes have been analyzed. The article presents data on preoperative management of patients with concomitant lung pathologies and a high risk of postoperative pulmonary complications, assessment of the risk of developing these complications based on evaluation of the functional status of patients. It analyzes the contemporary recommendations on the perioperative prevention of pulmonary complications, the use of physical exercises and respiratory gymnastics in the perioperative period in patients with a high risk of postoperative pulmonary complications. It is concluded that the implementation of comprehensive strategy aimed at reducing the risk of pulmonary complications should ensure decrease in their frequency and mortality due to them.